Promoting translanguaging (or not) in the ESP classroom: An analysis of monoglossic and heteroglossic practices and discourses. (July 2022) - Cots, Josep M.; Gallego-Balsà, Lídia; Llanes, Àngels
Abstract: The idea of translanguaging as a potential resource for language and content learning runs counter to "the monolingual principle" (Cummins, 2009), according to which languages should be taught separately in order to (a) avoid interference from other languages and (b) increase the learners exposure to the target language. This study has two main goals: (i) characterise the classroom practices and discourses of two instructors in line with their respective monoglossic or heteroglossic perspective in the context of a university course module on business English; (ii) provide empirical evidence for the impact of translanguaging practices in the form of language learning outcomes. The analysis is mainly based on observations and audiovisual recordings of classroom sessions and the students' performance before and after a 16-week teaching intervention.